A longitudinal study of persistent smoking among HIV-positive gay and bisexual men in primary relationships. (March 2017) - Gamarel, Kristi E.; Neilands, Torsten B.; Conroy, Amy A.; Dilworth, Samantha E.; Lisha, Nadra; Taylor, Jonelle M.; Darbes, Lynae A.; Johnson, Mallory O.
Abstract: Introduction: We examined the stability of smoking behaviors, and factors associated with persistent smoking in a longitudinal study of HIV-positive gay and bisexual men in primary relationships. Methods: A sample of 377 HIV-positive men on antiretroviral therapy and their same-sex partners completed five assessments over two years. Participants completed semi-structured interviews which assessed smoking status, sociodemographic factors, relationship dynamics, and HIV-related disease characteristics. Latent transition analysis estimated the amount of transition in smoking over time. Latent class analysis examined factors associated with smoking status across the study period. Results: At baseline, 28.1% ( n = 106) of participants reported current smoking. Over 90% of the HIV-positive men remained in the same smoking category over time (68.4% persistent non-smokers; 24.1% persistent smokers). Men whose partners smoked and men with lower income had higher odds of being persistent smokers, whereas older men and men who identified as Latino race/ethnicity had lower odds of being persistent smokers compared to non-smokers. Conclusions: Despite efforts to reduce smoking among people living with HIV (PLWH), a substantial subset of men continued to smoke during their two years in the study. Findings suggest that primary partners who also smoke and low income were the strongest predictors of sustained smoking behaviors among HIV-positive men. Additional research is needed to better understand how to increase motivation and support for smoking cessation among PLWH and their primary partners, while attending to how socioeconomic status may inhibit access to and the sustained impact of existing smoking cessation programs. Highlights: At baseline, over one-quarter of men in relationships reported smoking. The majority of men remained smokers during the two years of the study. Partners who smoke and low income were the strongest predictors of persistent smoking.